Keabsahan Akad Transaksi Jual Beli dengan Sistem Dropshipping dalam Perspektif Ekonomi Islam - Mohammad Jauharul Arifin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Selling and buying with the dropshipping system is a new buying and selling practice among the people. This buying and selling allows the seller to sell items that he does not already own, and the buyer makes prepayments. In simple terms, this dropshipping system is defined as buying and selling where the seller does not have merchandise in stock and the buyer places an order and payment in advance. After receiving an order from the buyer, then the seller will buy the order from the producer or supplier to send the order to the buyer. The sale and purchase of dropshipping has caused many polemics regarding the legal status and validity of the transaction. Buying and selling is prone to fraud and obscurity so that many people prohibit buying and selling using this system. The purpose of this study is to focus on seeing the legal status and validity of contracts in buying and selling using the dropshipping system. In this study, researchers used qualitative research methods with descriptive analysis. The results of this study indicate that buying and selling with the dropshipping system is permitted in Islam by using the salam contract and it can be said that the transaction does not cause gharar (obscurity) and uses the salam buying and selling contract (buying and selling orders). This research is a qualitative research with descriptive analysis supported by literature review from several literatures to reveal the validity of the sale and purchase transaction contract with the dropshipping system in the Islamic economic perspective.